Hub-and-spoke cartels: Theory and evidence from the grocery industry - Robert Clark; Ignatius J. Horstmann; Jean-François Houde (Queen's University, Department of Economics, 2021)
Numerous recently uncovered cartels operated along the supply chain, with firms at one end facilitating collusion at the other - hub-and-spoke arrangements. These cartels are hard to rationalize because they induce double marginalization and higher costs. We examine Canada's alleged bread cartel and provide the first comprehensive analysis of hub-and-spoke collusion. We make three contributions: i) Using court documents and pricing data we provide evidence that collusion existed at both ends of the supply chain, ii) we show that collusion was effective, increasing inflation by about 40% and iii) we provide a model explaining why this form of collusion arose.
Keywords: L41; L44; L12; L13; D22; L66; 330; antitrust; vertical collusion; grocery industry